Short-term foreign trips correlates of the four factors model of cultural intelligence - Bhawana Bhardwaj (Rajagiri Management Journal (RAMJ), 2022)
Purpose: In today's global business environment, international assignments have become integral part of employee's job profile. Adaptation to a different cultural environment plays a role in affecting employee's performance. In such a situation, cultural intelligence plays an important role. In order to sustain in a diverse work setting, a global organization entails managers who are sensitive to different cultural requirements. Factors affecting cultural intelligence have been a major area of study. However, studies relating short-term foreign trips and their role on four aspect of cultural intelligence are lacking. Therefore, present study was undertaken to know role of foreign visits in affecting cultural intelligence among professionals of diverse background. Design/methodology/approach: The present study is a primary study conducted for a sample of 120 respondents divided into two groups. One group comprised professionals having experience of foreign visits while other group comprised professionals who had not visited a foreign country. We use Levene's Test for equality of variances was applied to assess the difference of variation of cultural intelligence between two different groups of respondents. Findings: The results revealed that short-term trips play a significant role in affecting metacognitive, cognitive and motivational components of cultural intelligence. However, behavior cultural intelligence is not affected by short-term trips significantly. Research limitations/implications: Outcome of present research forms basis for future studies that can be conducted linking long-term trips and culture intelligence. This study is practically useful for improving cultural intelligence of professionals to enhance their success and effectiveness in international assignments. Originality/value: The study adds novelty to the field of cultural intelligence as prior studies were lacking in relating role of short-term trips on four different components of cultural intelligence.
Keywords: 650; Cultural intelligence; Foreign trips; International business; Culture